Thursday

March 26, 2015

March 26, 2015

Posted by **RANDA** on Tuesday, June 21, 2011 at 12:07pm.

- math -
**MathMate**, Tuesday, June 21, 2011 at 12:49pmGiven f(x) = x2 – 12x + 36

and f(x)=25, equate:

25 = x² - 12x + 36

x²-12x+11=0

(x-11)(x-1)=0

therefore x=11 or x=1

**Answer this Question**

**Related Questions**

math - Given the quadratic function f(x) = x2 – 18x + 81, find a value of x such...

math - Given the quadratic function f(x) = 16x^2 – 64x + 64, find a value of x ...

math - Given the quadratic function f(x) = 16x2 – 64x + 64, find a value of x ...

math - Given the quadratic function f(x) = 16x2 – 64x + 64, find a value of x ...

algebra - given the quadratic function f(x) 4x^2 -24x +36 find the value of x ...

algebra - Given the quadratic function f(x)=9x^2-36x+36 find a value of x such ...

Algebra2 - Complete parts a – c for each quadratic function: a. Find the y-...

Maths - It is given a quadratic function y=a(x-h)62+k.If its graph is a parabola...

math - determine the value of k such that g(x)=3x+k intersects the quadratic ...

Algebra - Can you please help me with the following problems? Find the ...